IMPROVING EARLY IDENTIFICATION OF THE HIGH-RISK ELDERLY TRAUMA PATIENT EMERGENCY MEDICAL SERVICES - Abdullah Saud Alsafi; Saleh Barjas Alanazi; Ali Saud AlANAZi; Fawaz Fayez Alanazi; Fahad Enad Alanazi; Abdulrahman Saeed alrashedi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The rapid increase in the aging population has resulted in an increased occurrence of trauma among the elderly. Effective and timely identification of high-risk elderly trauma patients by emergency medical services (EMS) is essential to optimize patient outcomes. This essay aims to explore strategies for improving the early identification of high-risk elderly trauma patients by EMS. A comprehensive review of existing literature, including reputable journals, provides evidence-based recommendations for enhancing EMS protocols, training, and collaboration between EMS and hospitals. This paper emphasizes the importance of early identification, accurate triaging, and appropriate intervention to improve the care and outcomes of the high-risk elderly trauma population.